Analisis Dinamika Kepribadian pada Tokoh Tara dalam Novel Katarsis Karya Anastasia Aemilia - Dina Aprilia Dewi Sofiana; Zahra Kautsa Syadida; Eva Dwi Kurniawan (PT. PENERBIT TIGA MUTIARA, 2024)
The purpose of this study is to analyze the characteristics of the character Tara in the novel Katarsis by Anastasia Aemilia. The researcher uses Sigmund Freud's personality dynamics theory to examine Tara's traits that appear in Anastasia Aemilia's novel Katarsis. The work is a